Comparison of Psychological Well-being, Moral Foundations and Sense of Humor in Infertile and Fertile Couples - Maliheh Tofighi Naeim; Mohammad Mehdi Pasandideh; Adele Eisanazar (مجله دانشگاه علوم پزشکی گیلان)
Background Infertility is a major crisis for couples, causing anxiety in them. Infertile couples experience more psychological, marital, family, and social problems. Objective This study aims to compare psychological well-being, moral foundations, and sense of humor between fertile and infertile couples in Rasht, Iran. Methods In this causal-comparative study, 212 couples (106 infertile and 106 fertile) referred to Al-Zahra Hospital in Rasht in 2022 participated. Ryff’s psychological well-being scale, moral foundations questionnaire, and multidimensional sense of humor scale were used to collect data. For data analysis, the analysis of covariance was used in SPSS software, version 28. Results There was a significant difference between infertile and fertile couples regarding self-acceptance, positive relations with others, autonomy, and personal growth dimensions of psychological well-being and its total score, and also in the sanctity/purity dimension of moral foundations and the humor creativity and uses of humor for social purposes dimension of sense of humor. Conclusion Fertile couples in Rasht have significantly higher scores in some dimensions of psychological well-being, moral foundations, and sense of humor than infertile couples.